2021
DOI: 10.21037/jtd-20-2876
|View full text |Cite
|
Sign up to set email alerts
|

Response of upper and lower airway inflammation to bronchial challenge with house dust mite in Chinese asthmatics: a pilot study

Abstract: Background: Allergen nasal challenge can induce increase of eosinophils in sputum, but report about eosinophilic inflammation in upper airway after allergen bronchial challenge in Chinese asthmatics was rare. The article aims to evaluate response of upper and lower airways to house dust mite (HDM) allergen bronchial challenge. Methods: HDM allergen bronchial challenge was carried out in asthmatic patients with allergic rhinitis (AR). Bronchial methacholine challenge and blood test were performed before and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…1 Patients with AR may display bronchial hyperresponsiveness (BHR), predicting a subsequent asthma onset and bronchial inflammation. 2 Bronchial eosinophilic inflammation may be assessed by a surrogate marker, such as the fractional concentration of exhaled nitric oxide (FeNO). It has been reported that high FeNO levels in children with AR alone predict a further asthma onset.…”
Section: Introductionmentioning
confidence: 99%
“…1 Patients with AR may display bronchial hyperresponsiveness (BHR), predicting a subsequent asthma onset and bronchial inflammation. 2 Bronchial eosinophilic inflammation may be assessed by a surrogate marker, such as the fractional concentration of exhaled nitric oxide (FeNO). It has been reported that high FeNO levels in children with AR alone predict a further asthma onset.…”
Section: Introductionmentioning
confidence: 99%